2022
DOI: 10.1080/21645515.2022.2131168
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy in the refugee, immigrant, and migrant population in the United States: A systematic review and meta-analysis

Abstract: Refugees, immigrants, and migrants (RIM) in the United States (US) have been identified as an underimmunized population prior to the COVID-19 pandemic. Vaccine acceptance is critical to combat the public health threat incited by COVID-19 and other vaccine-preventable disease. To better understand escalating vaccine hesitancy among US RIM, a comprehensive evaluation of the problem and solutions is necessary. In this systematic review, we included 57 studies to describe vaccination rates, barriers, and intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 72 publications
4
21
0
Order By: Relevance
“…Our findings corroborate previous research that suggests trust in the host country’s government and public health authorities are key factors that affect migrants’ attitude towards COVID-19 vaccines and vaccination decision making (22, 30, 36, 49, 50). Lack of trust among migrant communities can stem from previous experience of xenophobia, racial discrimination, and anti-migrant politics (50, 51). A qualitative systematic review of COVID-19 vaccine hesitancy by Shearn et al showed that “feeling unheard, ignored or excluded from the healthcare system” caused institutional mistrust resulting in COVID-19 vaccine hesitancy among RIM populations (42).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings corroborate previous research that suggests trust in the host country’s government and public health authorities are key factors that affect migrants’ attitude towards COVID-19 vaccines and vaccination decision making (22, 30, 36, 49, 50). Lack of trust among migrant communities can stem from previous experience of xenophobia, racial discrimination, and anti-migrant politics (50, 51). A qualitative systematic review of COVID-19 vaccine hesitancy by Shearn et al showed that “feeling unheard, ignored or excluded from the healthcare system” caused institutional mistrust resulting in COVID-19 vaccine hesitancy among RIM populations (42).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that no additional demographic data beyond the aforementioned elements were collected following the MVP's community partner agencies' request. This decision was driven by the recognition that some communities harbor an inherent distrust toward the medical system (Daniels et al., 2022). In deference to the wisdom and preferences of the community partners, the MVP respected this request, prioritizing achieving higher vaccination rates over extensive data collection efforts.…”
Section: Interventionmentioning
confidence: 99%
“…Furthermore, some aspects are specific to having an immigrant background. A review of qualitative studies on vaccination hesitancy in immigrants during the vaccination rollouts for COVID-19, HPV, influenza, hepatitis B, and pneumococcal infections, found several determining factors such as a lack of knowledge of the vaccine's existence and function, misinformation, distrust of official institutions and cultural bias (8). Among these findings, a lack of knowledge of the existence of a vaccine and its main benefits could be considered especially alarming.…”
Section: Introductionmentioning
confidence: 99%